Combined fibre atrophy and decreased muscle regeneration capacity driven by mitochondrial DNA alterations underlie the development of sarcopenia. Issue 4 (28th June 2022) - Kimoloi, Sammy; Sen, Ayesha; Guenther, Stefan; Braun, Thomas; Brügmann, Tobias; Sasse, Philipp; Wiesner, Rudolf J.; Pla‐Martín, David; Baris, Olivier R.
Abstract: Background: Mitochondrial dysfunction caused by mitochondrial (mtDNA) deletions have been associated with skeletal muscle atrophy and myofibre loss. However, whether such defects occurring in myofibres cause sarcopenia is unclear. Also, the contribution of mtDNA alterations in muscle stem cells (MuSCs) to sarcopenia remains to be investigated. Methods: We expressed a dominant‐negative variant of the mitochondrial helicase, which induces mtDNA alterations, specifically in differentiated myofibres (K320E skm mice) and MuSCs (K320E msc mice), respectively, and investigated their impact on muscle structure and function by immunohistochemistry, analysis of mtDNA and respiratory chain content, muscle transcriptome and functional tests. Results: K320E skm mice at 24 months of age had higher levels of mtDNA deletions compared with controls in soleus (SOL, 0.07673% vs. 0.00015%, P  = 0.0167), extensor digitorum longus (EDL, 0.0649 vs. 0.000925, P  = 0.0015) and gastrocnemius (GAS, 0.09353 vs. 0.000425, P  = 0.0004). K320E skm mice revealed a progressive increase in the proportion of cytochrome c oxidase deficient (COX − ) fibres in skeletal muscle cross sections, reaching a maximum of 3.03%, 4.36%, 13.58%, and 17.08% in EDL, SOL, tibialis anterior (TA) and GAS, respectively. However, mice did not show accelerated loss of muscle mass, muscle strength or physical performance. Histological analyses revealed ragged red fibres but also stimulated regeneration, indicating activation of MuSCs. RNAseq demonstrated enhanced expression of genes associated with protein synthesis, but also degradation, as well as muscle fibre differentiation and cell proliferation. In contrast, 7 days after destruction by cardiotoxin, regenerating TA of K320E msc mice showed 30% of COX − fibres. Notably, regenerated muscle showed dystrophic changes, increased fibrosis (2.5% vs. 1.6%, P  = 0.0003), increased abundance of fat cells (2.76% vs. 0.23%, P  = 0.0144) and reduced muscle mass (regenerated TA: 40.0 mg vs. 60.2 mg, P  = 0.0171). In contrast to muscles from K320E skm mice, freshly isolated MuSCs from aged K320E msc mice were completely devoid of mtDNA alterations. However, after passaging, mtDNA copy number as well as respiratory chain subunits and p62 levels gradually decreased. Conclusions: Taken together, accumulation of large‐scale mtDNA alterations in myofibres alone is not sufficient to cause sarcopenia. Expression of K320E‐Twinkle is tolerated in quiescent MuSCs, but progressively leads to mtDNA and respiratory chain depletion upon activation, in vivo and in vitro, possibly caused by an increased mitochondrial removal. Altogether, our results suggest that the accumulation of mtDNA alterations in myofibres activates regeneration during aging, which leads to sarcopenia if such alterations have expanded in MuSCs as well.